Interaction of Hematological Analysis and α-globin Genotypes among Eligible Blood Donors - Teh , Lai Kuan; Lim, Li Fang; Teh, Yu Leong; George, Elizabeth; Lee, TzeYan; Lim, Lay Ngor (IIUM Medical Journal Malaysia, 2020)
Introduction: Alpha thalassaemia is one of the haemoglobin disorders in which the carriers of alpha thalassaemia may have normal haemoglobin level and are eligible to donate blood which may bring complications. This study is to investigate the interaction of haematological parameter with α-globin genotypes among eligible blood donors. Materials & Methods: A cohort study with 270 eligible blood donors were analysed for red cell indices. Alpha-globin (α-globin) genotyping was performed for seven deletions, six point mutations and two triplications. Statistical analyses were performed to compare the α-globin genotypes with haematological data. Results: High prevalence of α-thalassaemia carriers (7.7%, 21/270) was found among blood donors. All of them did not show anaemic pictures with a normal Hb level (>12 gm/dl). Five genotypes were identified consisting of 249 αα/αα (92.2%), nine -α 3.7/αα (3.3%), nine-- SEA/αα (3.3%), two -α 4.2/αα (0.7%) and one ααCS/αα (0.4%). Different α-globin genotypes showed a significant difference in RBC, MCV, MCH, MCHC, RDW, and Hct/Hb ratio (p<0.05) due to the different extent of α-globin chain reduction. Conclusion: Our study concluded that by using Hb level alone is not sufficient to screen for the eligibility of blood donors. Full blood count (FBC) screening with borderline MCV and MCH levels might be able to rule out silent α-thalassemia carriers. FBC and molecular characterisation should be incorporated together to properly rule out α-thalassaemia carriers.><0.05) due to the different extent of α-globin chain reduction. Conclusion: Our study concluded that by using Hb level alone is not sufficient to screen for the eligibility of blood donors. Full blood count (FBC) screening with borderline MCV and MCH levels might be able to rule out silent α-thalassemia carriers. FBC and molecular characterisation should be incorporated together to properly rule out α-thalassaemia carriers.